Assessment of market access for agricultural goods in the eu regional trade agreements - Dzyad Оlena (Technology audit and production reserves, 2016)
Based on the analysis of the tariff regime the assessment of market access for agricultural products in regional trade agreements (RTAs) with the EU was made. It was established that the principles of agricultural protectionism formed and continue to determine the development of the EU agricultural markets and the position of the EU in the RTAs. The majorities of the EU RTAs are signed and valid within the countries which aren’t strategic partners in agricultural trade. Their tariff regime is characterized by low rates with a high proportion of tariff lines which are not imposed by tariff and also by list of goods for which tariff quotas are fixed. For the EU strategic partners (which are currently trading with the EU in the standard GSP) high tariff rates are combined with a low percentage of tariff lines that are not imposed by tariffs. In case of signing RTAs there is a significant potential of liberalization of the tariff regime for them. Non-tariff instruments dominate in agricultural trade; they are approved and can be regulated by WTO rules. It is likely that regional multilateral agreements between the leading players will contribute not only «mitigate conflicts», but also to progress negotiations on agriculture in the WTO and the growth trade of agricultural products.